Foundations of Learning and Instructional Design Technology - West, Richard E> (Open textbook library., 2018)
This book received the 2018 AECT Outstanding Book Award! "What is this field?" "Where have we come from as a discipline, and where are we going?" "What do I want to study?" These and other questions are typical for new students in the field of Learning and Instructional Design Technology. This textbook is designed to help answer these questions and provide the quickest route to understanding the history and current trends in the field. After surveying classic theories and writings, as well as more recent applications of theory and practice, students will be better prepared to chart their own course and careers within the discipline. This book is designed to support foundations courses common in departments, as well as seminars on current trends and issues.